2016
DOI: 10.18632/oncotarget.8027
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of solid tumors using probiotic Symbioflor-2 - restraints and potential

Abstract: To date, virulent bacteria remain the basis of most bacteria mediated cancer therapies. For clinical application attenuation is required. However, this might result in a drastically lowered therapeutic capacity. Herein we argue that the E. coli probiotic Symbioflor-2, with a history of safe application may constitute a viable tumor therapeutic candidate. We demonstrate that Symbioflor-2 displays a highly specific tumor targeting ability as determined in murine CT26 and RenCa tumor models. The excellent specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
45
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 89 publications
1
45
0
2
Order By: Relevance
“…Особый интерес представляют результаты оценки противоопухолевого потенциала непатогенных бактерий -представителей собственной нормофлоры человека, а именно: Bifidobacterium spp., Lactobacillus spp. (анаэробы), Escherichia coli (факультативный анаэроб) [20][21][22][23]. Показано, в частности, что бактерии Bifidobacterium longum способны к транслокации из кишечника во внутреннюю среду организма с фиксацией в макрофагах печени, обеспечивая при этом высокий уровень колонизации опухоли молочной железы у крыс [20].…”
Section: Introductionunclassified
“…Особый интерес представляют результаты оценки противоопухолевого потенциала непатогенных бактерий -представителей собственной нормофлоры человека, а именно: Bifidobacterium spp., Lactobacillus spp. (анаэробы), Escherichia coli (факультативный анаэроб) [20][21][22][23]. Показано, в частности, что бактерии Bifidobacterium longum способны к транслокации из кишечника во внутреннюю среду организма с фиксацией в макрофагах печени, обеспечивая при этом высокий уровень колонизации опухоли молочной железы у крыс [20].…”
Section: Introductionunclassified
“…While it is also a Gram-negative facultative anaerobe, unlike S. typhimurium , it has non-pathogenic variants naturally found in the human gut (commensal strains, some of which are probiotics that have a positive effect on health when given) [68]. The ability to make use of these strains without further attenuation and their status as clinically approved probiotics makes them attractive candidates for use in therapies [69]. The most common probiotic strain in use is E. coli Nissle 1917, but alternative strains have been explored [41,69].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to make use of these strains without further attenuation and their status as clinically approved probiotics makes them attractive candidates for use in therapies [69]. The most common probiotic strain in use is E. coli Nissle 1917, but alternative strains have been explored [41,69]. While E. coli has been used more than S. typhimurium in the overall field of synthetic biology, Prindle et al demonstrated that significant genetic circuits built in E. coli could be transferred to the more clinically used S. typhimurium , noting that these two species have similar ease of engineering as they have fully sequenced genomes, knockout collections, and easily used tools for genetic manipulation [70].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found to prevent relapses of superficial bladder cancer to a high degree and has been deployed in the clinics already since the late 1980s. Further promising candidates for BMTT include Gram-positive bacteria like Listeria monocytogenes or Clostridium novyi-NT and Gram-negative bacteria like Salmonella Typhimurium and Escherichia coli (Paterson et al, 2010;Kubiak and Minton, 2015;Felgner et al, 2016a;Kocijancic et al, 2016). Although the concepts to apply the various bacteria for cancer therapy differ significantly, they have all been able to demonstrate antitumour properties in preclinical models and some even in clinical trials.…”
mentioning
confidence: 99%